Damage from predation on the reindeer husbandry area in Finland during the years 1976-83 - Nieminen, Mauri; Leppäluoto, Juhani (Rangifer, 1985)
During the years 1976-1983 predators killed a total of 8900 reindeer in Finland. The highest numbers of reindeer killed by predators were found in the marked areas of Inari, Kuusamo and Sodankyla and in the reindeer herding areas of Kasivarsi (a total of 873 reindeer), Kemi-Sompio (731), Lappi (658) and northern Salla (632). With the exception of the Kasivarsi reindeer herding area, predator damage was more or less concentrated on the reindeer herding areas on the eastern border. During 1977- 1982 the majority of reindeer killed by predators were hinds (49,6%) and calves (41,0%). Predators killed most reindeer in April-June. In May and June the majority of reindeer killed by predators were calves. During 1977-83 most reindeer were killed by wolves (27,6%). wolverine (25,4%), bear (24,8%) and eagles (14,5%). Wolves killed reindeer mainly in the autumn and early winter during the soft snow period. Wolverine and lynx killed reindeer in February-April in crusted snow conditions. Bears killed most reindeer during the calving period in May-June and reindeer killed by eagles were found in plenty in spring and summer.Petovahingot Suomen poronhoitoalueella vuosina 1976-83.Abstract in Finnish / Yhteenveto: Vuosina 1976-83 pedot tappoivat Suomessa yhteenså 8 900 poroa. Eniten petojen tappamia poroja lôytyin Inarin, Kuusamon ja Sodankylån merkkipiireisså sekå Kåsivarren (yhteenså 873 poroa), Kemin-Sompion (731), Lapin (685), ja Sallan pohjoisen (632) paliskunnissa. Kåsivarren paliskuntaa lukuunottamatta petovahingot keskittyivåt låhinnå itårajan paliskuntiin. Vuosina 1977-82 petojen tappamista poroista suurin osa oli vaatimia (49,6%) ja vasoja (41,0%). Eniten pedot tappoivat poroja huhti - kesåkuun aikana. Tuoko - ja kesåkuussa suurin osa petojen tappamista poroista oli vasoja. Vuosina 1977-83 eniten poroja tappoivat susi (27,6%), ahma (25,4%), karhu (24,8%) ja kokta (14,5%). Sudet tappoivat poroja pååasiassa syksyllå ja alkutalvella pehmeån lumen aikana. Ahma ja ilves tappoivat poroja helmi - huhtikuun hankikeleillå. Karhu tappoi eniten poroja vasonta-aikana touko - kesåkuussa, ja kotkan tappamia poroja lôytyi runsaasti kevåållå ja kesållå.Rovdjurskadorna inom Finlands renskötselområde under åren 1976-83.Abstract in Swedish / Sammandrag: Under åren 1976-83 dôdades i Finland 8900 renar av rovdjur. Flest rovdjursrivna renar påtråffades inom Enares, Kuusamos och Sodankylås màrkesdistrikt samt inom Kàsivarsis (sammanlagt 873 renar), Kemin-Sompios (731), Lappis (685) och Salla pohjoinens (632) renbeteslag. Fôrutom til Kàsivarsis renbeteslag koncentrerades rovdjursskadorna, framst till renbeteslagen vid ostgrånsen. Under åren 1977-82 var stôrsta delen av de rovdjursrivna renarna vajor (49,6%) och kalvar (41,0%). Flest renar dôdades av rovdjur under april-juni. Under maj-juni var stôrsta delen av de rovdjursrivna renar kalvar. Under åren 1977-83 dôdades flest renar av varg (27,6%), jarv (25,4%) bjôrn (24,8%) och orn (14,5%). Vargar dôdade renar huvudsakligen på hosten och i bôrjan av vintern, då snôn var som losast. Skadorna vållade av jarv och lo koncentrade sig framst till skarfôret i februari-april. Bjôrnen dôdade flest renar under kalvningstiden i maj-juni, medan ganska stort antal av ôrn dôdade renar påtråffades under våren och sommaren.